Discomforting surplus: gender, sexualization, and omissions in ethnographic fieldwork - Su, Phung N.; Su, Phi Hong (Frontiers in Sociology, 2023)
As sisters and sociologists, we shared an unnerving experience of sexual harassment in one of our preliminary field sites. Our research pursuits split thereafter, with one of us leaning into questions of gender and sexuality and the other steering clear. Despite our diverging interests, we both encountered discomforting moments that raise questions about what data we render surplus in our analysis. In this article, we draw on ethnographic and interviewing data from our respective projects to conceptualize “discomforting surplus” as ethnographic data that we omit from our analyses. We offer two types of discomforting surpluses: those that reveal dissonance between our actions and self-conceptions, and those that seem not just uncomfortable, but inconsequential. We mine these discomforting surpluses, calling for introspection about our subject positions and the potential benefits of trying out analytical frames we have ignored. We conclude with practical suggestions for reflecting meaningfully on our relationships to the field and engaging in thought experiments that center discomforting surplus. These contradictions, omissions, and unnerving questions in ethnographic research are important to grapple with as we encounter a push for greater transparency and open science.